Sexual Orientation Identity Development Milestones Among Lesbian, Gay, Bisexual, and Queer People: A Systematic Review and Meta-Analysis - Hall, William J.; Dawes, Hayden C.; Plocek, Nina (Frontiers in Psychology, 2021)
This paper is a systematic review and meta-analysis on sexual orientation identity development milestones among people who are lesbian, gay, bisexual, or another sexual minority identity (LGB+). Common milestones measured in the 30 studies reviewed were becoming aware of non-heterosexual attractions, questioning one’s sexual orientation, self-identifying as LGB+, coming out to others, engaging in sexual activity, and initiating a romantic relationship. Milestones occurred in different sequences, although attraction was almost always first, often followed by self-identification and/or sexual activity; coming out and initiating a romantic relationship often followed these milestones. Meta-analysis results showed that the mean effect sizes and 95% confidence intervals varied by milestone: attraction (M age = 12.7 [10.1, 15.3]), questioning one’s orientation (M age = 13.2 [12.8, 13.6]), self-identifying (M age = 17.8 [11.6, 24.0]), sexual activity (M age = 18.1 [17.6, 18.6]), coming out (M age = 19.6 [17.2, 22.0]), and romantic relationship (M age = 20.9 [13.2, 28.6]). Nonetheless, results also showed substantial heterogeneity in the mean effect sizes. Additional meta-analyses showed that milestone timing varied by sex, sexual orientation, race/ethnicity, and birth cohort. Although patterns were found in LGB+ identity development, there was considerable diversity in milestone trajectories.